#TITLE_ALTERNATIVE# - PUTRA ( NIM : 20211005)Pembimbing : Dr. rer. nat. Bobby Eka Gunara, IMANSYAH
In this thesis, we solve a static Maxwell’s equations for Schwarschild-(anti) de Sitter spacetime, known as the Kottler spacetime which satisfy Einstein’s condition. We are used the potential form to solve the Maxwell’s equations and considering the generalized Lorentz gauge condition. The remaining coupling is simplified by using an ansatsz for potential. The resulting equations are a set of second order partial differential equations and we consider a separable solutions. The solutions is representing an electromagnetic fields on the black holes with certain characteristics.